Gravity drainage of a stratified profile - S. Awadalla, (1989)
The Green and Ampt approach was developed for the falling water table case following an initial sudden drop in the position of the water table. The analysis presents an approximate solution for one-dimensional flow in saturated porous media. The formulation is based on calculating the position of draining front with time and the cumulative outflow time relationships for stratified profile. The Green and Ampt results are checked by using data obtained from a well-proven computer-based numerical solution for unsaturated flow equation involving an implicit finite difference approach